Analysis of Water Quality Parameters for the Habitats of Caulerpa racemosa Seaweed at Joko Mursodo Beach, Lohgung, Lamongan. - Safitri, Elok; Rachmadiarti, Fida (LenteraBio : Berkala Ilmiah Biologi, 2023)
The growth of Caulerpa racemosa is almost evenly distributed in Indonesian waters, one of which is found on Joko Mursodo beach which has a sandy beach substrate so that it fits the habitat of Caulerpa racemosa. One of the important things that must be considered in the cultivation of Caulerpa racemosa is water quality, because water quality plays an important role in the successful growth of seaweed. In this regard, it is necessary to study the water quality at Joko Mursodo Lohgung beach, Lamongan to determine whether the water quality is in accordance with the requirements of good life for seaweed cultivation. This research method is observation with principal component analysis (PCA) for physico-chemical parameters of water. Water samples measured include the value of temperature, pH, salinity, dissolved oxygen, TTS and heavy metal pb levels at Caulerpa racemosa. The samples were taken from three stations with three repetitions at each station and measured in situ and in the laboratory. Water quality measurements refer to the quality standards of KMLH No.51 Thn 2004. The water quality of Joko Mursodo beach, Lamongan has several parameters that exceed the quality standards, namely TSS and temperature, but can still be tolerated by seaweed. While the PCA results show the point between parameters is not too far away which means between parameters are interrelated.